Investigasi Empiris: Tata Kelola Perusahaan dan Pengungkapan Sukarela pada Perbankan Syariah di Indonesia - Rokhaniyah, Siti (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2020)
This study investigated empirically the effect of good corporate governance on the level of voluntary disclosure in annual reports of Islamic banks. Corporate governance was proxied by managerial ownership, board of commissioners, audit committee, nomination and remuneration committee, integrated governance committee, corporate governance committee, risk management committee, risk monitoring committee, and institutional ownership. Samples are selected with criteria; a Sharia Commercial Bank (BUS) that was consistent in publishing annual reports in 2016-2019. There are 13 BUS that meet the criteria. Data were analyzed using panel data regression (fixed effect) with an error tolerance of 5%. Based on the results of the regression analysis it was concluded that managerial ownership, the board of commissioners, the audit committee, the nomination and remuneration committee, and the integrated governance committee had a positive effect on the level of voluntary disclosure. Meanwhile, the risk management committee and risk monitoring committee negatively impact to the level of voluntary disclosure. The corporate governance and institutional ownership committee has no effect on the level of voluntary disclosure in annual Islamic banking reports. Theoretically, these findings have implications for adding literature on corporate governance and voluntary disclosure in Islamic banking, which has so far focused on qualitative descriptive methods. On a practical level, these findings are useful for executives in Islamic banking, particularly in implementing good corporate governance and voluntary disclosure policies.